The Effectiveness of Remedial Learning in Improving Islamic Religious Education Learning Outcomes in Class XII Motorcycle Engineering SMK Negeri 6 Samarinda Academic Year 2022/2023 - Hermansyah, Hermansyah (PT Literasi Nusantara Publisher, 2022)
This study discusses the relevance of remedial learning with students achievements in Islamic religious education at SMK Negeri 6 Samarinda, the research is included in the type of field research using quantitative analysis. The results showed that: Remedial study in class XII Motorcycle Engineering SMK Negeri 6 Samarinda is in the high category with the value 79, is in the interval of 78-81. Learning outcomes of Islamic education students of class XII Motorcycle Engineering SMK Negeri 6 Samarinda is in the high category with a value of 88, located at intervals of 87-89. Results of analysis on the inferential statistics i.e. test T, derived Thitung hypothesis test result (t0) = 7.98 > of this = 2.09. So, H0 on reject and H1 accepted. It can thus be concluded that, using a simple regression formula, there is an influence of remedial learning on the learning outcomes of Islamic religious education in class XII Motorcycle Engineering SMK Negeri 6 Samarinda.